Contribution to the validation of the expectancy-value scale for primary school students - Peixoto, Francisco (2022)
Grounded in ‘expectancy-value’ theory, this paper reports on the psychometric properties of an instrument intended to measure students’ motivation in mathematics. The participants were 2045 third-, fourth- and fifth-grade students from Estonia, Finland, Norway, Portugal, Serbia and Sweden. The Expectancy-Value Scale (EVS) was found to be suitable for early grades of primary education in measuring competence self-perceptions and subjective task values relative to the mathematics field. The results indicate a good model fit aligned with the expectancy-value theory. The EVS dimensions showed good reliability, and scalar invariance was established. However, findings also indicated high correlations between some of the EVS dimensions, which is well documented for students at this age. The findings are discussed relative to the ‘expectancy-value’ theory framework and students’